1988
DOI: 10.1007/bf01871392
|View full text |Cite
|
Sign up to set email alerts
|

Influence of serosal Cl on transport properties and cation activities in frog skin

Abstract: The effects of serosal substitution of isosmotic Na2SO4-Ringer solution for NaCl-Ringer solution were studied in the short-circuited frog skin (Rana pipiens, Northern variety). Despite prompt changes of transepithelial measurements, initial cellular effects were slight. After 30 to 45 min, however, the transcellular current had decreased and the cell electrical potential had depolarized, in association with decrease of the apical membrane fractional resistance and basolateral membrane conductance. Apical membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1991
1991
1992
1992

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Response to O-Clb. Previous studies have shown that 0-Clb depolarizes the apical membrane during the same period that we observed induction of K ÷ secretion (Biber et al, 1985;Duffey et al, 1986;Costa et al, 1987;Klemperer and Essig, 1988; Leibowich et al, 1988). Thus it seemed reasonable that under control conditions, with large negative intracellular voltages (Nagel, 1976;Helman and Fisher, 1977), K ÷ secretory rates are extremely low because K ÷ is near electrochemical equilibrium across the apical membrane, and exposure to 0-Clb could "induce" K ÷ secretion simply by depolarizing the cell, thereby favoring K ÷ exit.…”
Section: Changes Of the Lntracellular Voltage (Va)supporting
confidence: 64%
See 1 more Smart Citation
“…Response to O-Clb. Previous studies have shown that 0-Clb depolarizes the apical membrane during the same period that we observed induction of K ÷ secretion (Biber et al, 1985;Duffey et al, 1986;Costa et al, 1987;Klemperer and Essig, 1988; Leibowich et al, 1988). Thus it seemed reasonable that under control conditions, with large negative intracellular voltages (Nagel, 1976;Helman and Fisher, 1977), K ÷ secretory rates are extremely low because K ÷ is near electrochemical equilibrium across the apical membrane, and exposure to 0-Clb could "induce" K ÷ secretion simply by depolarizing the cell, thereby favoring K ÷ exit.…”
Section: Changes Of the Lntracellular Voltage (Va)supporting
confidence: 64%
“…There are four known effects of 0-Clb on principal cells: (a) intracellular voltage depolarizes (see above; Biber et al, 1985;Duffey et al, 1986;Costa et al, 1987;Klemperer and Essig, 1988;Liebowich et al, 1988); (b) intracellular [CI-] and [Na ÷] decrease (Ferreira and Ferreira, 1981;Giraldez and Ferreira, 1984;D~Jrge et al, 1985;Biber et al, 1985); (c) cell volume is reduced (Ussing, 1965;Ferreira and Ferreira, 1981); and (d) intracellular pH rises (Civan and Peterson-Yantorno, 1986). Any or all of these could play a role in the induction of K ÷ secretion.…”
Section: Mechanism Of Induction Of K + Secretion By O-clbmentioning
confidence: 99%
“…and fR" GbK G ash + G hK ( 8) GaK, GaSh. GbK and Gp were calculated with equations 5-8 from experimental values for G t and fRn recorded in the absence and presence of Ba2+.…”
Section: Effect O F Serosal Tonicitymentioning
confidence: 99%
“…This long-time increase does not occur in gluconate solutions and depends on the presence of Cl" in the serosal bath and on the tonicity of the serosal solu tion. Effects of serosal tonicity and Cl" re placements on transepithelial Na+ transport have been the subject of several studies [7][8][9][10]. Microelectrode experiments [7][8][9] showed that a major part of the inhibition on Na+ transport following Cl" removal or after elevation of the serosal osmolality could be attributed to cell depolarization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation